2011
DOI: 10.1002/jbm.a.33197
|View full text |Cite
|
Sign up to set email alerts
|

Protection against titanium particle‐induced osteoclastogenesis by cyclooxygenase‐2 selective inhibitor

Abstract: Wear particle-induced osteoclastogenesis is the most common cause of aseptic loosening in total joint arthroplasty. Although cyclooxygenase (COX)-2, an inducible regulator of prostaglandin E2 (PGE2) synthesis, is known to be involved in osteoclast differentiation, its effect on osteoclastogenesis in response to wear particles remains unclear. In this study, we investigated the role of COX-2 in the regulation of osteoclast differentiation in the osteoclast precursor cell line RAW264.7 stimulated with titanium (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
10
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 41 publications
(74 reference statements)
1
10
0
Order By: Relevance
“…Infiltration of multinucleated osteoclast in model and peri-prosthesis tissue has been well defined, and our previous work confirmed that Ti particles significantly increased osteoclastogenesis in vivo and in vitro 891213. Therapeutic strategy targeting osteoclast formation significant inhibits particle-associated bone resorption1013.…”
Section: Discussionsupporting
confidence: 53%
See 2 more Smart Citations
“…Infiltration of multinucleated osteoclast in model and peri-prosthesis tissue has been well defined, and our previous work confirmed that Ti particles significantly increased osteoclastogenesis in vivo and in vitro 891213. Therapeutic strategy targeting osteoclast formation significant inhibits particle-associated bone resorption1013.…”
Section: Discussionsupporting
confidence: 53%
“…Briefly, there are three important events in wear particle-induced-osteolysis, including chronic inflammation, osteoclast formation, and osteoclastic bone resorption5678910111213. Particles worn from prosthesis are easily phagocytized by the peri-prosthetic phagocytes in the tissue4.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…To understand the biology between wear debris and aseptic loosening, we and others previously investigated how wear debris affects osteoclast stimulation. 17, 18 However, particle exposure not only has a direct effect on bone homeostasis by stimulating osteoclastogenesis, but also has adverse effects on osteoblastogenesis. 19 Recent studies demonstrated that marked impairment of bone formation from reduced osteoblast activity was a common feature of peri-prosthesis in wear particle-induced osteolytic bone disease.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, wear particles may cause adverse biological reactions in the following order: inflammation, increased osteoclastogenesis, and subsequent osteoclastic bone resorption [11]. Since osteoclastogenesis and osteoclast activation play essential roles in wear particles-induced osteolysis, inhibiting osteoclastogenesis and osteoclast function should be an important therapeutic strategy for the treatment of aseptic loosening after total joint replacement [12,13].…”
Section: Introductionmentioning
confidence: 99%